PENDIDIKAN USIA DINI MENURUT AL-QUR’AN (KAJIAN SURAT AN-NUR AYAT 58-59) - Nurjaman (JEDLISH : Journal Of Education and English Language Teaching, 2023)
Educating children from an early age is an important and fundamental milestone for a child's life, and has a major influence on subsequent child development. In educating children, we still encounter many parents (educators) who are ambitious and force their young children to have more abilities, without paying attention to the level of development and abilities of the children. On the contrary, many parents are indifferent to their children's education without regard to values important Islamic teachings regarding child education. Based on the background of the problems above, the formulation of the problem is as follows: 1) when did education begin to be given to children, 2) what educational aspects are contained in Surah An-Nur verses 58-59. The purpose of writing this thesis is: 1) to find out the early stages of educating children, 2) to find out the educational aspects contained in Surah An-Nur verses 58-59. The methods used in this study are deductive and inductive methods, namely methods used to collect and analyze general data to make specific conclusions, and specific data to general conclusions. The data was obtained using literature study techniques and documentation techniques from various premier sources, namely the actual Al-Qur'an and Al-Hadith regarding the educational aspects contained in Surah An-Nur verses 58-59. After the data is collected, it is then interpreted and analyzed using logic supported by Islamic education as an analytical tool. After being analyzed, the following conclusions are obtained: 1) educating children begins with selecting a mate, during the womb and after birth, 2) the educational aspects contained in Surah An-Nur verses 58-59 are: the obligation of parents to educate their children from the early age, namely by getting used to the child to always ask permission from parents at three times, namely: before the dawn prayer, at midday, and after evening.